PENGARUH BAURAN PEMASARAN PERGURUAN TINGGI TERHADAP KEPUASAN DAN DAMPAKNYA KEPADA LOYALITAS MAHASISWA PADA TIGA PTS TERKEMUKA DI KOTA BANDUNG - Elisabeth Koes Soedijati (Bina Ekonomi, 2011)
The aim of this study is to obtain  the description of the impact of the marketing mix towards the satisfaction  and  loyalty of students of the three distinguished universities in Bandung.  It deals with variables of: (1) marketing mix of higher education,  (2) students  satisfaction, (3) the loyalty of students. This research  employed  the survey method with quantitative  approach. From the  total population of 1753 students, 95 participated  in the survey and  they comparised  of students majoring  in accounting, class 2007/2008  in the bachelor’s  degree program  in-the faculty of economics. The results showed  that the seven sub-variables of marketing mix would have  impacts on the student satisfaction, even though only six of them showed significance. The order of the sub-variables with significant  effect based on the student  satisfaction  is: (1) the product/ service  of the schools  with ρyx1 = 0,5152;  (2) service price of the school with ρyx2 = 0,2222; (3) school location with ρyx3= 0,2152; (4) the process/ management of school  service with ρyx4 = 0.2132 ; (5) physical evidence  of facilities and infrastructure  with ρyx6 = 0.1732 ; (6) human resources with ρyx5 = 0,1592. The accumulative  amount of the impact of those variables  towards student  satisfaction  is 97%,  while  the last 3% is the effects of other  factors out of the scope of this study. School promotion would  also effect student satisfaction, yet it was insignificant. Student satisfaction would lead significantly  towards  their loyalty with ρzy = 0,8452 = 71,40%, while  the last 28,60%  is the impact caused by other  factors not  in the scope of this study.